Valuasi Ekonomi Dan Dampak Lingkungan Akibat Industri Pengolahan Marmer Di Desa Besole Kabupaten Tulungagung Di Tinjau Dari ESDAL Perspektif Islam - Silfi Indririyani; Moh. Qudsi Fauzy (Jurnal Ekonomi Syariah Teori dan Terapan, 2016)
The existence of the marble processing industry in Tulungagung Besole village has an impact both economic and environmental impact.This study calculating the economic valuation of the marble industry tod eterminethefeasibility of the industry when seenin the economic and environmental impact generated by natural resource economics review Islamic perspective. Use of ESDAL Islamic perspective is intended to determine how the rules of Islam in governing the use and maintenance of nature, and to know if the marble business in the village Besole have run the rule.Results of the study found that the marble processing industry economically feasible. However, theprocessing of marble that have a negativeimpact on the environment and society, like a air pollution, pollution caused by solid waste, and also a form of energy that is noise pollution